A novel analysis of spun yarn hairiness inside limited two-dimensional space. Issue 21 (November 2019) - Xia, Zhigang; Liu, Xin; Wang, KeZuo; Deng, Bo; Xu, Weilin
Surface hairiness of spun yarns is critical to the yarn post-processing deficiency and resultant fabric quality. Several test methods are available for measuring yarn hairiness but they cannot detect the accurate hair amount and precise hair length. This paper provides a novel method to perform accurate hairiness tests on the spun yarn. A new test apparatus was devised by installing a blowing pipe outside of the hairiness testing area comprising a projection receiver and a corresponding laser. The rectangle end plane of the blowing pipe air inlet is vertical to the laser plane and tangent to the edge line of the projection receiver surface. Pressure generated through this inlet stretches yarn wild hairiness straightly in one direction, and fully maps accurate hairiness amount and length configuration on the projection receiver surface. The subsequent measurement showed that this novel test apparatus detected more hairiness with improved accuracy in both number and length of hairiness. Approximately real gravimetric hairiness weight can be obtained by this method which is impracticable for other conventional photoelectric apparatus.